Quenching of the quantum p-strength in light exotic nuclei - E. Cravo; R.B. Wiringa; R. Crespo; A. Arriaga; A. Deltuva; M. Piarulli (Physics Letters B)
One-nucleon spectroscopic overlaps, their strength or spectroscopic factors (SFs), and nucleon removal cross sections for light nuclei in the mass range A≤12 were evaluated using the fully correlated Quantum Monte Carlo (QMC) wave functions (WFs). Harder (AV18+UX) and softer (NV2+3) bare interactions were used providing consistent results. The SFs were also taken from simple Shell Model (SM) calculations. This structure information was incorporated in the standard three-body Faddeev/Alt-Grassberger-Sandhas reaction formalism to evaluate the (p,pN) cross sections. The results further our understanding of the quenching of the quantum p-shell strength obtained from structure and reactions. We have found the ratios of the total QMC sums of SFs to the SM ones to be uniform and ∼ 3/4. The corresponding ratios of the sums Below Particle Threshold (BPT) of SFs, as well as of total cross sections, deviate strikingly from the uniform trend in some special cases. We find these ratios to be close to unit for Li9→8Li+n and C9→8B+p. In contrast, they are strongly reduced for C11→10C+n and B11→10Be+p mirror transitions, resulting from the quenching of the strength for low-lying 2+ final state transitions. The QMC theoretical cross section BPT for C11(p,pn) is about two times smaller than the experimental data.